FINANCIAL PERFORMANCE ANALYSIS USING ECONOMIC VALUE ADDED (EVA) AND FINANCIAL VALUE ADDED (FVA) AT PT. ASTRA INTERNATIONAL TBK 2017-2021 PERIOD - Nurul Fauziah; Agung Widhi Kurniawan; Nurman; Anwar; Andi Mustika Amin (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study aims to assess the financial performance of PT. Astra International Tbk during the 2017-2021 period by employing the Economic Value Added (EVA) and Financial Value Added (FVA) metrics. The type of research used in this study is descriptive research utilizing a quantitative approach. The population of this study consists of all the financial report data of PT. Astra International Tbk from 2017 to 2021, while the samples include the statements of financial position and profit/loss statements. The data collection technique employed is documentation. The collected data was analyzed using the EVA and FVA calculations. The findings of this study indicate that PT. Astra International Tbk demonstrated positive results in terms of financial performance when measured using EVA, indicating their ability to generate economic value added. Similarly, when measured using FVA, PT. Astra International Tbk achieved positive results, signifying their ability to generate financial value added. Overall, PT. Astra International's performance can be characterized as commendable.